The Effect of Disgust and Fear Modeling on Children’s Disgust and Fear for Animals - Askew, Chris (American Psychological Association, 2014)
Disgust is a protective emotion associated with certain types of animal fears. Given that a primary function of disgust is to protect against harm, increasing children’s disgust-related beliefs for animals may affect how threatening they think animals are and their avoidance of them. One way that children’s disgust beliefs for animals might change is via vicarious learning: by observing others responding to the animal with disgust. In Experiment 1, children (ages 7–10 years) were presented with images of novel animals together with adult faces expressing disgust. Children’s fear beliefs and avoidance preferences increased for these disgust-paired animals compared with unpaired control animals. Experiment 2 used the same procedure and compared disgust vicarious learning with vicarious learning with fear faces. Children’s fear beliefs and avoidance preferences for animals again increased as a result of disgust vicarious learning, and animals seen with disgust or fear faces were also rated more disgusting than control animals. The relationship between increased fear beliefs and avoidance preferences for animals was mediated by disgust for the animals. The experiments demonstrate that children can learn to believe that animals are disgusting and threatening after observing an adult responding with disgust toward them. The findings also suggest a bidirectional relationship between fear and disgust with fear-related vicarious learning leading to increased disgust for animals and disgust-related vicarious learning leading to increased fear and avoidance.